2005
DOI: 10.1074/jbc.m408862200
|View full text |Cite
|
Sign up to set email alerts
|

Exercise Stimulates Pgc-1α Transcription in Skeletal Muscle through Activation of the p38 MAPK Pathway

Abstract: Peroxisome proliferator-activated receptor ␥ co-activator 1␣ (PGC-1␣) promotes mitochondrial biogenesis and slow fiber formation in skeletal muscle. We hypothesized that activation of the p38 mitogen-activated protein kinase (MAPK) pathway in response to increased muscle activity stimulated Pgc-1␣ gene transcription as part of the mechanisms for skeletal muscle adaptation. Here we report that a single bout of voluntary running induced a transient increase of Pgc-1␣ mRNA expression in mouse plantaris muscle, co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
485
2
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 607 publications
(527 citation statements)
references
References 49 publications
37
485
2
3
Order By: Relevance
“…For instance, ionomycin (an agent that increases membrane permeability to Ca 2+ ) or electrical stimulation-induced increases in PGC-1α expression in rat muscle cell cultures has shown to be reduced or abolished when co-treated with KN-62 (CaMK inhibitor) or cyclosporin A (calcineurin inhibitor), respectively (Kusuhara et al, 2007). Similar findings were reported in the study by Ojuka et al (2003) where co-treatment with caffeine and KN-93 (a CaMK inhibitor) abolished the caffeine mediated increases in CS activity and protein expressions of ALAS, COX1 and Cyt c. While calcineurin is suggested to induce PGC-1α by activating CREB through MEF2 (Akimoto et al, 2005), it is well regarded that CaMK predominantly acts through the p38 mitogen activated protein kinase (p38 MAPK) pathway, which in turn activates the transcription factor activating transcription factor 2 (ATF2) in inducing PGC-1α and mitochondrial biogenesis (Akimoto et al, 2005;Wright et al, 2007a). Indeed, increased expressions of PGC-1α, COX1, ALAS and CS, along with p38 MAPK and ATF2 phosphorylation were evident in rat epitrochlearis muscles following caffeine incubation (Wright et al, 2007a).…”
Section: Calciumsupporting
confidence: 76%
“…For instance, ionomycin (an agent that increases membrane permeability to Ca 2+ ) or electrical stimulation-induced increases in PGC-1α expression in rat muscle cell cultures has shown to be reduced or abolished when co-treated with KN-62 (CaMK inhibitor) or cyclosporin A (calcineurin inhibitor), respectively (Kusuhara et al, 2007). Similar findings were reported in the study by Ojuka et al (2003) where co-treatment with caffeine and KN-93 (a CaMK inhibitor) abolished the caffeine mediated increases in CS activity and protein expressions of ALAS, COX1 and Cyt c. While calcineurin is suggested to induce PGC-1α by activating CREB through MEF2 (Akimoto et al, 2005), it is well regarded that CaMK predominantly acts through the p38 mitogen activated protein kinase (p38 MAPK) pathway, which in turn activates the transcription factor activating transcription factor 2 (ATF2) in inducing PGC-1α and mitochondrial biogenesis (Akimoto et al, 2005;Wright et al, 2007a). Indeed, increased expressions of PGC-1α, COX1, ALAS and CS, along with p38 MAPK and ATF2 phosphorylation were evident in rat epitrochlearis muscles following caffeine incubation (Wright et al, 2007a).…”
Section: Calciumsupporting
confidence: 76%
“…The correlations between PGC-1α and rodent muscle oxidative capacity, and between PGC-1α and both GLUT4 and FAT support the idea that in lean and obese muscles PGC-1α is central to a coordinated metabolic programme that upregulates a number of genes simultaneously to produce an oxidative muscle phenotype that relies extensively on blood-borne substrates for energy provision [3,5,31]. The small range of PGC-1α protein abundance across a range of heterogeneous muscles implies that small, physiologically induced changes in PGC-1α protein [6,30,32,33] can have pronounced effects on muscle metabolism, as shown by the present study and others [3,16].…”
Section: Characterisation Of Lean and Obese Zucker Ratsmentioning
confidence: 63%
“…The activation of AMPK, calcium/calmodulin-dependent protein kinase (CaMK), calcineurin A (CnA), and p38 mitogen-activated protein kinase (MAPK) signaling cascades are well-known upstream regulators of PGC-1␣ expression in skeletal muscle (2,17,43). In addition, we have previously shown that ␤ 2 -AR activation is required for low-intensity exercise-induced PGC-1␣ expression (26), especially for that of PGC-1␣-b and PGC-1␣-c (25).…”
Section: Discussionmentioning
confidence: 99%